THE GLOBAL AND LOCAL ERRORS IN ENGLISH-INDONESIAN TRANSLATION - Ikmal Muhammad; Suratman Dahlan (Universitas Khairun, 2019)
ABSTRACT: This research aims at revealing and analyzing errors made by the fourth-semester students of English Education Study Program, Khairun University. Dulay, Burt, and Krashen (1982) categorized errors into two types, namely global and local errors. Global errors refer to errors that affect overall sentence organization significantly hinder communication. While, errors that affect single element (constituents) in sentences do not usually hinder communication significantly are called local errors. The scholar focuses on analyzing students’ errors in translating legal terms in English into Indonesian. This research is qualitative research that is analyzed the data descriptively. The research shows that there are many errors occurred in students’ target-language text. The errors made by the students dominantly indicate local errors with the percentage of 81.57% as the errors which do not influence or disturb the readers’ understanding. While, global errors’ percentage is 18.43%.